(untitled) (MAUSAM, 1989)
The work presents an empirical model for wave-field in Bombay High Area (.BHA) based on data from 1976 to 1985 for the May-October when the conditions generally exceed the critical limits of the operations of the rigs. I is seen that in non-cyclonic conditions during May-October, among various forms of relationships between windspeed and wave-heights, the linear fit are found to be quite adequate for the purposes of forecasting mean-height. A study of direction of waves and their steadiness is also dealt with.